Variations in estimates of underweight, stunting, wasting, overweight and obesity in children from Argentina comparing three growth charts - Padula, Gisel (2012)
Objective: To compare estimates of underweight, stunting, wasting, overweight and obesity based on three growth charts. Design Cross-sectional study to estimate weight-for-age, length/height-for-age and weight-for-height comparing the 2006 WHO Child Growth Standards ('the WHO standards'), the 1977 National Center for Health Statistics (NCHS) international growth reference ('the NCHS reference') and the 1987 Argentine Pediatric Society Committee of Growth and Development reference ('the APS reference'). Cut-off points were defined as mean values ±2 s d. Epi-Info software version 6·0 (Centers for Disease Control and Prevention) was used for statistical evaluations (χ 2, P ≤ 0·05). Setting Greater La Plata conurbation, Buenos Aires, Argentina. Subjects A total of 2644 healthy, full-term children from 0 to 5 years of age. Results Prevalence of underweight was higher with the WHO standards than with the other references up to the first 6 months. For the rest of the ages, prevalence was lower with the WHO standards. Stunting prevalence was higher with the WHO standards at all ages. Prevalence of wasting was higher with the WHO standards compared with the NCHS reference up to the first 6 months and lower at 2-5 years of age. Overweight and obesity prevalences were higher with the WHO standards at all ages. Conclusions The new WHO standards appear to be a solid and reliable tool for diagnosis and treatment of nutritional diseases, also being the only one built with infants fed according to WHO recommendations. Therefore, our results support the decision of the National Ministry of Health about the utilization of the new WHO standards to monitor the nutritional status of Argentinean children aged less than 5 years.